Blended teaching versus traditional teaching for undergraduate physiotherapy students at the University of the Witwatersrand - Sadiya Ravat; Paula Barnard-Ashton; Monique M. Keller (AOSIS, 2021)
Background: Shifting from face-to-face teaching to incorporating technology may prepare students better for future work as health professionals. Evidence of blended teaching's effect on the academic performance of undergraduate physiotherapy students' performance is scarce. Objective: The purpose of our study was to determine students' theoretical and clinical performance in a blended teaching module compared to their own performance in two knowledge areas taught face to face, and student perceptions of blended teaching in the third-year physiotherapy curriculum. Methods: The cross-sectional study design included 47 third-year physiotherapy students. The orthopaedic module was delivered using a blended teaching approach in two consecutive semesters, whilst two other physiotherapy knowledge areas, neuromusculoskeletal and cardiopulmonary, in the same semesters were delivered face to face. Theoretical and clinical performances of students were compared for significance and effect. Students were assessed on their theoretical and clinical knowledge in all areas using the same assessment methods. The students (n = 43) also completed a survey on their blended teaching experience. Results: Significantly higher theoretical marks for orthopaedics were calculated compared to neuromusculoskeletal and cardiopulmonary for both semesters with a large positive effect (average Cohen d = 4.44) for blended teaching on theoretical examination performance; no statistically significant difference for clinical performances. Students felt engaged in the blended teaching process, and 72% preferred blended teaching over face-to-face teaching or online delivery. Conclusion: Blended teaching improved the theoretical marks, demonstrating that knowledge acquisition was improved, but not clinical performance. Clinical implications: The study contributes to the knowledge base of blended learning in Health Science Education in South Africa. The authors identified a gap where future studies should investigate the effect of blended learning on clinical performance outcomes as a continuation from this one.